China’s innovation model- lessons and applicability in Africa - Oluwole Nurudeen Omonijo; Yunsheng Zhang (Cogent Economics & Finance)
Scholars and innovation economists are of the view that knowledge and technological externalities are what spur innovation in the knowledge-based global economy of today. Africa has been in a prime position to take advantage of technological advancements to boost economic competitiveness. This study analyzed how African states can benefit from the Chinese innovation model. We used data spanning from 2010 to 2023 from the Global Innovation Index and the ordinary least squares (OLS) econometric technique as an analysis framework to examine the model and variables. Interestingly, we discovered that the core challenges faced by Africa in terms of innovation were a result of deficiencies in the same core elements that China has adopted to spur innovation. The results further showed that all the variables suchch as education, human development, R&D spending, R&D tax incentives, subsidies and technology spillovers through FDI are positive factors that enhance innovation. Our findings suggest African countries should prioritize regional partnerships and integration in science and technology, investment in research and development, and the development of technology clusters to foster collaboration and knowledge sharing.